2019
DOI: 10.3390/ijerph16214117
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Physical Fitness among Overweight and Non-Overweight Austrian Secondary School Students

Abstract: The aim of the study was to evaluate factors associated with physical fitness (PF) among overweight and non-overweight Austrian secondary school students. PF was measured using the German motor test (DMT) 6–18 and students were asked about sex, migration background, weekly leisure time physical activity and daily electronic media use. In total 560 adolescents (56.6% female) with a mean age of 15.4 ± 1.4 years and a mean body mass index (BMI) of 22.5 ± 4.2 kg/m² were evaluated with 130 (23.2%) students classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…The present study showed that both malnutrition and overnutrition have adverse effects on physical fitness, which is consistent with previous studies [27,28]. The prevalence of stunting and underweight in 1985 was 10.3% and 1.7%, respectively, and the prevalence of overweight and obesity combined was 0.9%; the former was likely the cause of the decline in physical fitness.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that both malnutrition and overnutrition have adverse effects on physical fitness, which is consistent with previous studies [27,28]. The prevalence of stunting and underweight in 1985 was 10.3% and 1.7%, respectively, and the prevalence of overweight and obesity combined was 0.9%; the former was likely the cause of the decline in physical fitness.…”
Section: Discussionsupporting
confidence: 92%
“…Gender and age were the important predictor variables for all four physical fitness indicators. As existing studies have only explored the relationship between sitting time, lifestyle habits, sedentary behavior and physical fitness performance [22,24,25], our findings can provide more information about association between lifestyle and physical fitness performance.…”
Section: Discussionmentioning
confidence: 83%
“…The research design of this study is similar to that of some of the existing studies that used regression models to evaluate the influence of various lifestyle habits on physical fitness using cross-sectional data through regression models [24,55]. Therefore, the limitations of this study were the same as those of the studies using cross-sectional data, in that we estimated the influence factors and speculated the possible effects, but this did not represent causal inference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations